Factors Influencing Success of Community Based Tourism: A Case Study of Ban Bang Nam Pueng Community in Samutprakarn Province - Thinothai, Kittipat; Vinijnaiyapak, Nattha (Dusit Thani College Journal, 2020)
This research aims to analyze the influence of factors on the success of CBT and propose guidelines for CBT development of Ban Bang Nam Pueng Community in Samutprakarn Province. This research used quantitative research conducting on questionnaires to collect data from 400 people living in Ban Bang Nam Phueng community. The sample size was determinated by Taro Yamane Formula. The statistical analysis Pearson Bivariate Correlation and Multiple Regression Analysis in Ordinary Least Squares (OLS). The research results show that Community Readiness, Community Engagement, Public Participation and Tourism Policy Framework Factors have a significant influence on The Success of Community Based Tourism, excepting Living Time in Community Variables that is in Community Engagement Factor hasn’t a significant influence on The Success of Community Based Tourism. For guidelines for CBT development should rely on community leaders to communicate information, push participation and build trust with people in the area to create a collaborative work.